AKTIVITAS KOMUNIKASI DINAS PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK DALAM MEWUJUDKAN PROGRAM KECAMATAN RAMAH ANAK DIKECAMATAN PASIR PENYU - Aditya Dwi Prasetyo; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Indragiri Hulu Regency is one of the districts that received the title of Madya as a child-friendly district in 2019, and the Pasir Penyu District is a pilot sub-district for other sub-districts. But in getting this award, there are still many problems that occur in the Pasir Turtle District, including cases of juvenile delinquency and molestation of minors, this case always increases every year from 2017 to 2019, therefore the Women Empowerment and Protection Agency makes The Task Force for the creation of a Child Friendly District Program to reduce problems that occur in Indragiri Hulu Regency               This study used a qualitative research method. Research sites at the Department of Women Empowerment and Child Protection, Indragiri Hulu District and Pasir Penyu District and the surrounding communities. Data collection techniques were carried out by means of observation, interviews and documentation. To achieve the validity of the data in this study, researchers used participation extension and triangulation               Based on the technical analysis above, the researchers assessed and concluded that the communication activities carried out by the task force unit in realizing the Child Friendly District program were several ways, namely socialization, supervision, and making facilities and infrastructure in the Pasir Penyu sub-district to support the realization of the Child Friendly District program in the District. Turtle Sand. The purpose of creating a Child Friendly District is to shape children's character to be even better and have noble character.  Keyword : Activitie, Programs, Child Friendly